Oral Isotretinoin-Associated Ocular Effects and Risk Factors: A Cross-Sectional Study - Abuallut II; Dibaji MQ; Assiri A; Mawkili W; Najmi AY; Ageeli SA; Hamdi AA; Ayoub RA; Muyidi AY; Hakami HT; Alhazmi AK; Rekini MH (Clinical Ophthalmology)
Ismail I Abuallut,1 Mohammed Q Dibaji,2 Ahmad Assiri,3 Wedad Mawkili,4 Ahmed Y Najmi,5 Safa Abdu Ageeli,5 Amaal Abdulaziz Hamdi,5 Raum Abdu Ayoub,5 Abdulaziz Yahya Muyidi,5 Hussam T Hakami,5 Abrar Khalid Alhazmi,5 Moayad Hassan Rekini5 1Department of Surgery, Ophthalmology Division, Jazan University, Jazan, Saudi Arabia; 2Prince Mohammed Bin Nasser Hospital - Jazan Health cluster, Jazan, 82943, Saudi Arabia; 3Department of Dermatology, Faculty of Medicine, Jazan University, Jazan, Saudi Arabia; 4Department of Pharmacology and Toxicology, College of Pharmacy, Jazan University, Jazan, Saudi Arabia; 5Faculty of Medicine, Jazan University, Jazan, Saudi ArabiaCorrespondence: Ismail I Abuallut, Ophthalmology Division, Jazan University, Jazan, Saudi Arabia, Email iabuallut@gmail.comPurpose: Oral isotretinoin is a derivative of vitamin A, used to treat acne vulgaris. One of its effects is altering the corneal surface and ocular glands, resulting in eye dryness and various other symptoms. This study aimed to analyze the impact of systemic isotretinoin treatment on ocular health and investigate the potential risk factors contributing to ocular pathology.Patients and Methods: This cross-sectional study was conducted on 489 participants in the Jazan region using a convenience sampling method. An online questionnaire composed of five sections, including the Arabic version of the validated Ocular Surface Disease Index (OSDI), was used to assess the presence of ocular symptoms associated with isotretinoin usage as well as the potential contributing risk factors.Results: A significant association was established between oral isotretinoin use and specific eye symptoms, including a gritty feeling in the eye (66.4%), sore eyes (68.6%), blurry vision (75.9%), and the need for moisturizing drops (35%). OSDI severity varied according to isotretinoin usage status, with severe OSDI grades reported in 56.9% of current users, 51.2% of those who stopped < 2 months ago, and 38.8% of those who stopped ≥ 2 months ago. Furthermore, significant risk factors associated with worse OSDI grades included contact lens use and isotretinoin dose, with contact lens use being associated with a 17.5-point increase in OSDI scores, while each 10 mg increase in isotretinoin dose was linked to a 0.20-point rise in OSDI score.Conclusion: This study emphasizes the importance of assessing individual risk factors before starting isotretinoin therapy and monitoring ocular health in patients undergoing therapy. Clinicians should be aware of preventive methods and should consider high-risk patients to an ophthalmologist for interventions, such as punctal plugs, that can reduce complications. Further research targeting specific populations with shared risk factors is needed to validate these findings.Keywords: retinoids, ocular pathology, eye dryness, Saudi Arabia